FACTORS AFFECTING STRESS LEVELS IN TYPE 2 DIABETES PATIENTS UNDERGOING DIET AT THE JOMBANG COMMUNITY HEALTH CENTER - Hawara, Gian (STIKes Mitra Keluarga, 2026)
Background: Type 2 diabetes mellitus is a chronic disease that requires long-term health management. Stress in patients with type 2 diabetes mellitus consists of several factors including: age, duration of treatment, diet, wound healing, and complications of diabetes mellitus. Stress, both physical and psychological, can activate the neuroendocrine system and sympathetic nerves through the hypothalamus, pituitary, adrenals, which causes an increase in the hormone cortisol which increases blood sugar levels in patients with diabetes mellitus. Objective: to analyze the factors that influence stress levels in patients with type 2 diabetes mellitus in undergoing a diet at the Jombang Community Health Center. Method: with a quantitative approach with a correlational analytical design and a cross-sectional approach. The study sample consisted of 116 respondents selected using a purposive sampling technique. Data collection used the Diabetic Knowledge Questionnaire (DKQ-24), The Self-Management Dietary Behaviors Questionnaire (SMDBQ), and a questionnaire on stress levels undergoing a diet. Bivariate analysis used the Chi-Square Test with a significance level of alfa = 0.05. Results: It is known that the factors that influence the level of stress in type 2 DM patients in undergoing a diet at the Jombang Community Health Center are knowledge factors with P-value = 0.034 and self-management P-value = 0.009, while the results on the age factor with P-value = 0.30, gender with P-value = 0.451, education with P-value = 0.095 and duration of suffering from DM with P-value = 0.092. Conclusion: that there is a relationship between the level of knowledge and self-management with the level of stress in type 2 diabetes mellitus patients in undergoing a diet at the Jombang Community Health Center.